Pengaruh Gaya Kepemimpinan dan Motivasi dalam Suatu Organisasi - Sulis Tyaningsih; Kun Nurachadijat (Departement of Mathematics Education, 2023)
Leadership is one’s ability to influence or motivate others to do something in accordance with a common goal. Leadership encompasses the process of influencing in determining the organization’s goals, motivating the behavior of its followers to the goals, influenced to improve the group and its culture. Motivation is a combination of desire and energy to a specific goal. Influencing someone’s motivation means making them do what we want them to do. Since the primary function of leadership is to lead, the ability to influence people is important. Leadership and motivation are two different things, although they have links in the work context and interpersonal organizational interactions. Keith Davis argued that without leadership, organizations are just a chaotic, disorderly group of human beings, and will not be able to generate purposeful behavior. Leadership is the human factor that binds a group together and gives it motivation toward specific goals, both in the short and long term. This means that between leadership and motivation there is a strong link.